A Novel Low Stiffness Air Spring Vibration-Isolation Mounting System - Chang-geng Shuai; Bu-yun Li; Jian-guo Ma; Zhao-hao Yang (Shock and Vibration)
Quasi-zero-stiffness (QZS) structures offer substantial practical benefits for facilitating the essential support and isolation of vibrational source loads aboard modern marine vessels. In order to design a compact QZS system of high bearing capacity, the article proposes a low stiffness air spring (LSAS) vibration-isolation mounting system composed of both vertical and lateral air springs. The vertical air springs support the load and isolate vibrations in the vertical direction, while the lateral air springs support the load and isolate transversal vibrations. Theoretical analyses based on a simple two-dimensional, single degree of freedom model demonstrate that the proposed novel LSAS design decreases the degree of stiffness in the support structure that would otherwise be induced by introducing lateral air springs and accordingly increases the vibration isolation effect. Moreover, optimization of the air spring parameters enables the lateral air springs to provide negative stiffness and thereby realize QZS characteristics. Experimental testing based on prototypes of a standard air spring mounting system and the proposed LSAS mounting system demonstrates that the stiffness of the proposed system is about 1/5 that of the standard system. Accordingly, the proposed structure design successfully alleviates the undesirable influence of lateral air springs on the stiffness of the mounting system.